Depoliticisation through employability: entanglements between European migration and development interventions in Tunisia - Jung, Alexander (Journal of ethnic and migration studies, 2022)
Accompanied by public demands to reduce migration by creating perspectives 'at home', employability projects have become an important component of migration and development policies. While research has revealed the sedentarism underlying these policies and questioned the effectiveness thereof, more recent work has found that stakeholders are, in fact, aware of the potential increase of migration. However, contrary to analyses that hold that such interventions are carried out because they meet the different interests of both migration and development actors, this paper argues that migration and development interventions are mutually implicated. Examining European employability projects in Tunisia and drawing on interviews with representatives of donors and implementing organisations as well as policy documents, this paper argues that employability activities operate through twofold depoliticised logics. Whereas the focus on employability enables isolating migration from politicised debates across Europe, these interventions promote depoliticised logics of neoliberal selectivity. In centring skills in these interventions, some subjects are rendered employable for the Tunisian and, potentially, European labour market. Others, in turn, are excluded from the participation in migration and development due to a lack of sought-after skills.